Two new bridges over the River Vardar in Skopje - Markovski Goran; Docevska Marija; Markelj Viktor (Građevinski Materijali i Konstrukcije, 2022)
This paper presents some aspects of the design of two new bridges over the River Vardar in Skopje. "Mihajlo Apostolski" is an integral bridge, consisting of two separate structures (22.05 + 50.50 + 21.05 m = 93.6 m length and 15.3 m width). The bridge deck is made up of a two-cell prestressed cast-in-situ box girder with a parabolically variable cross section. The abutments and the piers are wall-shaped and supported on single and double row piles, respectively. The side spans, together with the approaching structures, were proposed to be built on traditional scaffolding, while the middle span over the minor riverbed was built with a free cantilever method. The extradosed bridge at Ljubljanska Street is 27.5 + 56 + 27.5 m = 111 m long and 24.1m wide. The ribbed deck (two post-tensioned main girders, cross girders, and deck slab) is supported from above by 32 parallel stay cables. The 12.6 m high pylons are located at the intermediate supports. In the base, the four piers have a rectangular cross section that has been rotated 45 degrees. The superstructure is supported by pot bearings. A deep foundation on piles was chosen. Cast-in-place construction of the superstructure was foreseen. The design of the bridges was done according to Eurocodes and respecting the fib and PTI recommendations. Detailed numerical analysis was carried out in the FEM software SOFiSTiK and additional auxiliary software.